A Novel Brain–Computer Interface Virtual Environment for Neurofeedback During Functional MRI - Baqapuri, Halim I.; Roes, Linda D.; Zvyagintsev, Mikhail; Ramadan, Souad; Keller, Micha; Roecher, Erik; Zweerings, Jana; Klasen, Martin; Gur, Ruben C.; Mathiak, Klaus (Frontiers in Neuroscience, 2021)
Virtual environments (VEs), in the recent years, have become more prevalent in neuroscience. These VEs can be programmed to offer great flexibility, replicability and control over the presented stimuli in an immersive setting. With recent developments it has become feasible to achieve higher quality visuals and VEs at a reasonable investment. Our aim in this project was to develop and implement a novel real-time functional magnetic resonance imaging (rt-fMRI) based neurofeedback (NF) training paradigm, taking into account new technological advances that allow us to integrate complex stimuli into a visually updated and engaging VE. We built upon and developed a first-person shooter (FPS) in which the dynamic change of the VE was the feedback variable in the brain-computer interface (BCI). We designed a study to assess the feasibility of the BCI in creating an immersive VE for NF training. In a randomized single blinded fMRI-based NF-training session, 24 participants were randomly allocated into one of two groups: active and non-active NF. All participants completed three runs of the shooter-game VE lasting 10 minutes each. Brain activity in a supplementary motor area (SMA) region of interest (ROI) regulated the possible movement speed of the player’s avatar and thus increased the reward probability. The gaming performance revealed that the participants were able to actively engage in game tasks and improve across sessions. All 24 participants reported being able to successfully employ NF strategies during the training while performing in-game tasks with significantly higher perceived NF control ratings in the NF group. Spectral analysis further showed significant differential effects on brain activity in the target region between the groups. The self-assessment manikin ratings showed an increase in arousal. Arousal has been linked to presence, or feelings of immersion, supporting the VE’s objective. Long paradigms, such as NF in MRI settings can lead to mental fatigue, therefore, VEs can help overcome such limitations. The rewarding achievements from gaming targets can lead to implicit learning of self-regulation and may broaden the scope of NF applications.